Calcium-binding properties, stability, and osteogenic ability of phosphorylated soy peptide-calcium chelate - Kong, Xiao; Xiao, Ziqun; Chen, Yuhang; Du, MengDi; Zhang, Zihui; Wang, Zhenhua; Xu, Bo; Cheng, Yongqiang; Yu, Tianying; Gan, Jing (Frontiers in Nutrition, 2023)
Bioactive peptides based on foodstuffs are of particular interest as carriers for calcium delivery due to their safety and reliance. The phosphorylated peptide has been reported to enhance calcium absorption and bone formation. Here, we introduced a novel complex of a peptide derived from soybean protein with phosphorylation modification. The mechanism, stability and osteogenic differentiation bioactivity of the peptide with or without calcium were studied. The calcium-binding capacity of phosphorylated soy peptide (SPP) reached 50.24±0.20μg/mg. The result of computer stimulation and vibration spectrum showed that SPP could chelate with calcium by phosphoric acid group, carboxyl oxygen of C-terminal Glu, Asp and Arg and phosphoric acid group of Ser on the SPP peptide at a stoichiometric ratio of 1:1, resulting in the formation of complex of ligand and peptide. Thermal stability showed that chelation enhanced peptide stability compared to SPP alone. Additionally, the in vitro studies showed that SPP-Ca could facilitated osteogenic proliferation and differentiation ability. Therefore, phosphorylation modification is a novel way to increase the bioavailability of calcium and phosphorylated SPP could function as a promising alternative to current therapeutic agents for bone loss.